Impact of analysis interval size on the quality of optical frequency domain imaging assessments of stent implantation for lesions of the superficial femoral artery. Issue 4 (12th August 2016) - Miki, Kojiro; Fujii, Kenichi; Kawasaki, Daizo; Shibuya, Masahiko; Fukunaga, Masashi; Imanaka, Takahiro; Tamaru, Hiroto; Sumiyoshi, Akinori; Nishimura, Machiko; Horimatsu, Tetsuo; Saita, Ten; Kobayashi, Yuhei; et al.
Abstract : Objectives: This study aimed to investigate the influence of analysis interval size on optical frequency domain imaging (OFDI) assessment of stent therapy for lesions of the superficial femoral artery (SFA). Background. No consensus or validating data are available with respect to the methodology of intravascular imaging analysis for the peripheral arteries. Methods. OFDI was performed for 30 SFA lesions, during endovascular therapy and at the 6‐month follow‐up. Initially, lumen and stent borders were traced at 1‐mm axial intervals. Volumes were calculated using a PC‐based software, and the volume index (VI) was defined as the volume divided by the stent length. Two additional OFDI analyses were performed using 2‐mm and 5‐mm intervals, thereby reducing the number of cross‐sectional image frames analyzed. Results. The mean stent length was 89.7 ± 35.2 mm. The mean difference in baseline minimum lumen area (MLA) was 0.4 mm 2 between MLA values from the 1‐mm and 2‐mm interval analyses, and 2.2 mm 2 between MLA values from the 1‐mm and 5‐mm interval analyses. In volumetric analysis, there were excellent correlations and good agreements for stent, lumen, and neointimal VI measurements obtained on the basis of different analysis intervals. Conclusions. Using large intervals in OFDI analyses of SFA lesions resulted in few differences in measurement variability of volumetric parameters. However, planar analysis for MLA assessment can be susceptible to high variability when large intervals are applied. © 2016 Wiley Periodicals, Inc.